Felt seismicity associated with shale gas hydraulic fracturing: The first documented example in Europe. Issue 23 (11th December 2014) - Clarke, Huw; Eisner, Leo; Styles, Peter; Turner, Peter
Abstract We describe the origin of felt seismicity during the hydraulic fracturing of the Carboniferous Bowland Shale at the Preese Hall 1 exploration well near Blackpool in the UK during 2011. The seismicity resulted from the interaction of hydraulic fracturing and a fault, the location of which was unknown at the time but has subsequently been located and does not intersect the well borehole. Waveform cross correlation is used to detect 50 events in the sequence. A representative hypocenter and strike‐slip focal mechanism is calculated using the best recorded seismic event. The hypocenter is calculated to lie 300–400 m east, and 330–360 m below the injection point and shown to lie on a fault imaged using 3‐D seismic at a depth of about 2930 m. The 3‐D survey shows that not only the event hypocenter but also the focal mechanism correlates strongly with a subsequently identifiable transpressional fault formed during the Late Carboniferous (Variscan) basin inversion.